Aspek Komunitas dan Institusi dalam Resiliensi Kampung Kota Yogyakarta - Damanik, Imelda I.; Setiawan, Bakti; Roychansyah, M. Sani; Usman, Sunyoto (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 7 No 1 (2020): April 2020DO - 10.24843/JRS.2020.v07.i01.p04, 2020)
Urban Kampung is an urban area with distinctive characters. The symbols as a poor, dense, and slum area, put the urban kampung as a high priority task for the government to solve. But besides that, the urban kampung demonstrates the capacity of the local community and institutions. Vulnerability aspects embedded with capacity aspects, build configuration that complements one to another, and build the distinctiveness in the context of resilience. As part of the urban area, urban kampung has to bring out its local resilience value to support urban resilience. This paper will provide an analysis of the resilience’s value by measuring the aspects of the communities and institutions of urban kampung in Yogyakarta. This research was conducted by distributing questionnaires that are compiled on a Likert scale in five urban kampungs in Yogyakarta City. The results are analyzed using the Principle Component Analysis (PCA), which will show the genetics distance and the relation between variables of the community aspects and the institutional aspects of the urban kampung . The PCA’s outcome of community and institutional aspects will be useful in designing public spaces in urban kampung as an effort to increase urban resiliency. Keywords : urban kampung ; community; institution; resilience; principal component analysis   Abstrak Kampung Kota adalah ruang perkotaan yang memiliki karakter yang khas. Simbol miskin, padat dan kumuh membentuk kampung kota menjadi pekerjaan rumah yang harus diselesaikan oleh pemerintah kota. Namun disamping itu, kampung kota hadir dengan kekuatan komunitas dan institusi lokalnya. Aspek-aspek pembentuk kerentanan (vulnerability) berdampingan dengan aspek-aspek pembentuk kapasitas (capacity) , saling mengisi dan membentuk kekhasan dalam konteks resiliensi. Sebagai bagian dari wilayah perkotaan, kampung harus menunjukkan nilai seberapa resiliensi aspek-aspek tersebut. Tulisan ini akan memberikan telaah mengenai perhitungan nilai resiliensi aspek komunitas dan institusi kampung kota di Yogyakarta. Penelitian ini dilakukan dengan menyebar kuestioner yang disusun dengan skala Likert di 5 kampung kota di Yogyakarta. Hasilnya kemudian akan dianalisis dengan Komponen Fundamental (Principal Component Analysis, PCA), yang akan menunjukkan jarak genetika dan relasi antara variabel aspek komunitas dan aspek institusi kampung kota. Temuan komponen fundamental aspek komunitas dan institusi akan bermanfaat dalam mendesain ruang publik dalam kampung kota dalam upaya peningkatan resiliensi kota. Kata kunci : kampung kota; komunitas; institusi; resiliensi; analisis komponen fundamental